2021
DOI: 10.3390/f12091259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acacia mangium Canopy on Physicochemical Characteristics and Nutrient Concentrations of the Soil at Ayer Hitam Forest Reserve, Malaysia

Abstract: The establishment of an Acacia mangium plantation often alters physicochemical characteristics and nutrient concentrations of soils. We aimed to evaluate the invasive potential of A. mangium forest on the soil in Ayer Hitam Forest Reserve, Peninsular, Malaysia. To achieve the mentioned target, four different regions, namely, the open ground region (OG), Acacia mangium region (AM), transition region (TZ), and native forest region (NF), were selected and each of the regions was divided into six plots. Composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 89 publications
0
6
0
1
Order By: Relevance
“…Our results have demonstrated that Acacia invasion impacted N cycling but did not appear to significantly impact P cycling except for causing increased P addition in AMDF. We suggest that elevated N produced by Acacia invasion can result in an N/P imbalance [101] in the invaded habitats. This imbalance affects nutrient mineralization rates and carbon sequestration but may also impact soil microbial communities and nutrient pools [114].…”
Section: Cumulative Impacts Of Acacia Invasion On Leaf Litterfall Nut...mentioning
confidence: 85%
See 1 more Smart Citation
“…Our results have demonstrated that Acacia invasion impacted N cycling but did not appear to significantly impact P cycling except for causing increased P addition in AMDF. We suggest that elevated N produced by Acacia invasion can result in an N/P imbalance [101] in the invaded habitats. This imbalance affects nutrient mineralization rates and carbon sequestration but may also impact soil microbial communities and nutrient pools [114].…”
Section: Cumulative Impacts Of Acacia Invasion On Leaf Litterfall Nut...mentioning
confidence: 85%
“…Increased production of litter with high nutrient concentrations in the two Acacia-invaded habitats implies that Acacia invasion has major impacts on biogeochemical cycling [24,99], resulting in both high litter accumulation and an up-regulation of net primary productivity. One effect of the increased production of N-rich litter may be a transition to the more open biogeochemical cycling of N and increased organic and available N concentrations in the soil [32,[99][100][101] in response to Acacia invasion.…”
Section: Effects Of Acacia Invasion On Nutrient Addition From Leaf Li...mentioning
confidence: 99%
“…Cultivation of acacia species significantly restores nutrient cycling in degraded soils to improve their growth (Hamad-Sheip et al, 2021). Planting increased soil fertility in terms of nitrogen (N), potassium (P), and soil organic carbon (SOC) compared with adjacent control fields (Ahmed et al, 2020).…”
Section: Land-use/cover Change and Ecosystem Service Valuesmentioning
confidence: 99%
“…Planting increased soil fertility in terms of nitrogen (N), potassium (P), and soil organic carbon (SOC) compared with adjacent control fields (Ahmed et al, 2020). Soil pH, cation exchange capacity, and phosphorus were also improved in acacia fields compared with adjacent soils (Amare et al, 2022;Hamad-Sheip et al, 2021). Improving soil fertility in acacia fields leads to increased annual crop yields (Chanie and Abewa, 2021).…”
Section: Land-use/cover Change and Ecosystem Service Valuesmentioning
confidence: 99%
See 1 more Smart Citation